Interactions of high-order Bessel vortex beam with a multilayered chiral sphere: Scattering and orbital angular momentum spectrum analysis. (September 2018) - Qu, Tan; Wu, Zhensen; Shang, Qingchao; Wu, Jiaji; Bai, Lu
Highlights: The analytical solution to the interactions between an inhomogeneous optically active spherical particle and a high-order Bessel vortex beam are investigated. The internal field, near-surface field and scattered field are calculated numerically. Results indicate the OAM spectrum spreads significantly with the increase of the incident beam center position shift from the axis. Abstract: Analytical solution to the scattered field and near-surface field of a multilayered chiral sphere illuminated by a high-order Bessel vortex beam (HOBVB) are investigated. Using the vector wave theory, the expansion coefficients of a HOBVB in terms of spherical vector wave functions (SVWFs) are derived. Based on the fields expansion in each region and continuous boundary condition at each interface, the expansion coefficients of the sphere are solved by constructing the iterative form of the coefficients equations. Influences of the topological charge, half-cone angle and chirality on the scattering pattern of far region and near-surface field are analyzed in detail. In addition, the intensity and phase distributions at the transverse plane after interaction are presented for on- and off-axis incidences. Comparisons of orbital angular momentum (OAM) spectrum indicate that off-axis incidence results in topological charge shift from the incident case, and the farther from the axis and the more complex the particles, the more serious the phase distortion. The results provide insights into the scattering and light-matter interactions and may find important applications in optical propagation and multicasting optical communication.